The Need of Financial Literacy Proficiency Level for Generation Z Students at School - Frederika Widi Prihartanti; Wiedy Murtini; Mintasih Indriayu (Green Publisher Indonesia, 2022)
Financial Literacy has a significant role in the individual decision-making process. Existing studies have proven that that lower levels of financial literacy lead to irrational financial decisions funds as well as savings and debt. Basically, Indonesian students in PISA 2018 have the lowest mean scores compared to other countries. At the same time, there is no integration in Indonesia curriculum with financial education. This study focuses on a review of financial education used in the current literature as well as their corresponding limitations.